A STUDY OF COLLOQUIAL EXPRESSION IN DOCTOR ZHIVAGOS’ NOVEL BY BORIS PASTERNAK - Indah Afani; Evi Zulida; Fadlia Fadlia; Makhroji Makhroji; Imran Imran (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
The problem of this research is what types of colloquial expression found in Boris Pasternaks’ Novel and what are the dominant of colloquial expression found in Boris Pasternaks’ Novel. The purpose of this research are to identify colloquial expression in the novel. The research is accomplished by the researcher by reading the novel. The data are classified according to types of colloquial expression and the patterns of the colloquial expression are found after the classification. This research used qualitative research to analyze the data. Data source of this study is Boris Pasternaks’ Novel. Its title was Dr. Zhivago. It was published by the New American Library, Inc on 1957 years. Its was 909 pages. After the researcher read and analyzed the novel, the researcher found colloquial expression in the novel especially single words, clipped words, constraction and verb adverb combination. The researcher found 314 colloquial expression in the novel. There are single words totally 127, clipped words totally 1, constractions totally 40 and verb adverb combination totally 146. It can be said single words is more dominant of constraction, constractions is more dominant of clipped words. Verb adverb combination is the most dominant of all types. It can be concluded that the novel also uses colloquial expression in the sentence to find out the change in the language used. The researchers hopes for other researchers can develop the subject of this study better.